THE EFFECT OF INDUSTRIAL WORK PRACTICES AND VOCATIONAL COMPETENCIES ON WORK READINESS WITH MODERATION OF SELF EFFICACY IN CLASS XII STUDENTS OF ACCOUNTING SKILLS COMPETENCE AT SOUTH JAKARTA STATE VOCATIONAL HIGH SCHOOL - Pitaloka, Nadya; Sumiati, Ati; Respati, Dwi Kismayanti (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of industrial work practices, vocational competence, and self-efficacy on job readiness and the effect of industrial work practices and vocational competence on job readiness through self-efficacy. The population comes from students of Class XII Accounting Skills Competence at the South Jakarta State Vocational High School totaling 174 with a sample of 114. This research is a quantitative study with a survey method. The variables of work readiness and self-efficacy used data derived from the results of distributing questionnaires. While the variables of industrial work practice and vocational competence use data in the form of prakerin values and competency test scores. The results obtained, namely that there is a positive and significant influence on industrial work practices, vocational competence, and self-efficacy on job readiness partially, and there is a positive and significant influence on industrial work practices and vocational competence on job readiness through self-efficacy.